1998
DOI: 10.1037/h0080359
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment and identity formation in adopted and nonadopted young adults: Contributions of family environment.

Abstract: Adopted and nonadopted college students were compared on measures of overall adjustment and identity formation, and on perceptions of the general environment characterizing their families of origin. Although adjustment and identity formation were largely similar in the two groups, the family dynamics that predicted success differed for adoptees and nonadoptees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…Research has also indicated that family dynamics that predict positive outcomes differed in adoptive and non-adoptive families. Whereas greater family individuality and expressiveness were related to positive self-control ratings in non-adopted college students, higher levels of clarity and structure in organizing family activities and family expressiveness were related to more self-control in college students who were adopted (Kelly et al, 1998; see also Levy-Shiff, 2001).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Research has also indicated that family dynamics that predict positive outcomes differed in adoptive and non-adoptive families. Whereas greater family individuality and expressiveness were related to positive self-control ratings in non-adopted college students, higher levels of clarity and structure in organizing family activities and family expressiveness were related to more self-control in college students who were adopted (Kelly et al, 1998; see also Levy-Shiff, 2001).…”
mentioning
confidence: 89%
“…Adoptive families have been found to be more cohesive (i.e., emotionally closer) and less individuated (i.e., individual family members are less independent) than non-adoptive families (Hoopes, 1982(Hoopes, , 1990Kelly, Towner-Thyrum, Rigby & Martin, 1998;Sobol, Delaney, & Earn, 1994). Research has also indicated that family dynamics that predict positive outcomes differed in adoptive and non-adoptive families.…”
mentioning
confidence: 91%
“…Some studies compared adopted and non-adopted young adults, mainly focusing on mental health and psychological well-being; however, results of these studies are not consistent and have exhibited contradictory findings. On one hand, a number of studies demonstrated that adult adoptees are more likely to be at higher risk for psychopathological outcomes and lower level of psychological well-being (Cubito & Obremski Brandon, 2000;Cantor-Grace & Pedersen, 2007;Feeney, Passmore, & Peterson, 2007;Hjern, von Borczyskowski, Lindblad, & Vinnerljung, 2006;Levy-Shiff, 2001;Passmore, Fogarty, Bourke, & Baker-Evans, 2005;Tieman, van der Ende, & Verhulst, 2005), while other studies failed to find any differences in adjustment and in psychological wellbeing between adopted and non-adopted adults (Borders, Penny, & Portnoy, 2000;Feigelman, 2000;Irhammar & Bengtsson, 2004;Kelly, Towner-Thyrum, Rigby, & Martin, 1998;Smyer, Gatz, Simi, & Pedersen, 1998).…”
mentioning
confidence: 97%
“…Thus, it is possible that the greater economic and parental stability experienced by the adoptees protected them against depression. Indeed, a number of studies suggest that a wellfunctioning adoptive family can buffer the adoptee against negative psychosocial outcomes such as poor self-esteem (e.g., Kelly, Towner-Thyrum, Rigby, & Martin, 1998;Passmore, Fogarty, Bourke, & Baker-Evans, 2005). Powell and Afifi (2005) also found that adult adoptees were less likely to express feelings of loss if their adoptive families were open and accepting.…”
Section: Depression Emotional Arousability and Perceptions Of Parenmentioning
confidence: 99%